Wolfram syndrome: case report of two siblings with genetic analysis - Singh Kochar, Inderpal; Jain, Rakhi; Ramachandran, Smita (Pediatric Review: International Journal of Pediatric Research, 2019)
Wolfram syndrome (WS) is an autosomal recessive neurodegenerative disorder. Also known as DIDMOAD it can have variable clinical presentation at different age. We report two siblings with WS presenting at 6 and 5 years of age respectively. They presented with type I diabetes mellitus and optic atrophy. Both were compound heterozygotes for mutation on exon 8 of WS1 gene. A high index of clinical suspicion along with genetic analysis plays a key to definite diagnosis.